Sufistic metaphors in the song "Puja" by Rhoma Irama: A stylistic hermeneutic spiritual study - Hidayat, Yogi Fery (Jurnal Penelitian Humaniora, 2025)
This study analyzes the sufistic metaphors in the song "Puja" by Rhoma Irama using a stylistic spiritual hermeneutic approach. The song’s lyrics convey spiritual messages through metaphorical language that aligns with Sufi teachings, emphasizing themes such as divine love, self-reflection, and the pursuit of spiritual purity. This research aims to uncover how the song’s lyrics reflect Sufi teachings and the relationship between human experience and the divine. A stylistic analysis, including word choice, rhythm, and imagery, is conducted to understand how these elements contribute to conveying the song's spiritual depth. The findings indicate that "Puja" serves not only as a musical piece but also as a spiritual expression with profound value within the context of Indonesian cultural and religious traditions. Through these metaphors, the song enriches the listener’s spiritual journey by encouraging personal reflection and a closer connection with the divine.